The Relationship between Electronic Word of Mouth in Social Media Websites and Consumers’ Purchase Intention - Karunamoorthy, Harvinmoorthy; Kepal, Noreina (Research in Management of Technology and Business, 2021)
The effect of Electronic Word of Mouth (eWOM) on the purchase intentions of customers has long been acknowledged. But with the introduction of the social media website, eWOM has become a new dimension. Individuals were able to talk to numerous people on the Internet before this new development. The social media website allows users to talk on the Internet with friends and acquaintances. This new eWOM approach might be stronger when it comes to purchasing intentions. The change of word of mouth to eWOM seeks less understanding for the consumers on purchase intention. This study aims to discuss the eWOM within the context of social media website. Particularly, this study examines the relationship between eWOM in social media website and consumers` purchase intentions. Quantitative method was used to accumulate data by using questionnaire. A total of 100 respondents from Johor Bahru using convenience sampling had been collected in this study. The findings showed that eWOM in social media websites had a significant and strong correlation on consumers’ purchase intention. This findings might give marketers with useful information for establishing their long-term connections with customers within social media websites and for promoting selected items by using favourable eWOM.